TO PEDIATRIC FACULTY OF THE KUBAN STATE MEDICAL UNIVERSITY – 45 YEARS - S. N. Alekseenko; T. V. Gaivoronskaya; S. E. Gumenyuk; V. A. Shashel; A. V. Burlutckaya; V. A. Tarakanov; V. А. Porodenko; G. G. Muzlaev; Е. О. Boyko; S. N. Sakhnov (Кубанский научный медицинский вестник, 2017)
This article is dedicated to the 45th pediatric department's anniversary of the Kuban state medical university. It reflects the history and prospects for further development of the faculty. Each department of pediatric faculty cherishes its traditions and history.